Alishewanella solinquinati sp nov., isolated from soil contaminated with textile dyes - Kolekar, Yogesh M.; Pawar, Shrikant P.; Adav, Sunil S.; Zheng, Liu-Qiang; Li, Wen-Jun; Shouche, Yogesh S.; Dastager, Syed Gulam; Kodam, Kisan M. (Current Microbiology, 2013)
A novel Gram-negative, motile, rod-shaped, facultative anaerobic bacterial strain, KMK6(T), was isolated from soil contaminated with textile dyes from an industrial estate located at Ichalkaranji, Maharashtra, India, and its taxonomical position was established by using a polyphasic approach. The major cellular fatty acids included C-17:1 omega 8c, summed feature 3 (C-16:1 omega 7c and/or iso-C-15:0 2-OH), C-17:0, C-16:0,C- and C-18:1 omega 7c. The DNA G+C content of strain KMK6(T) was 48.8 mol %. 16S rRNA gene sequence analysis confirmed its placement in the genus Alishewanella, and exhibited sequence similarity levels of below 97 % to the type strains of validly published Alishewanella species. On the basis of genotypic and phenotypic evidence, strains KMK6(T) is considered to be a novel species of the genus Alishewanella, for which we propose that strain KMK6(T) (=NCIM 5295(T) =BCRC 17848(T)) is assigned to a novel species, Alishewanella solinquinati sp. nov.

Marine actinobacteria showing phosphate-solubilizing efficiency in Chorao Island, Goa, India - Dastager, Syed Gulam; Damare, Samir (Current Microbiology, 2013)
The occurrence and distribution of an actinobacteria group of bacteria capable of dissolving insoluble phosphates were investigated in this study in marine environments, especially in sediments of Chorao Island, Goa Province, India. A total of 200 bacterial isolates of actinobacteria was isolated. All isolates were screened for phosphate-solubilizing activity on Pikovskaya's agar. Thirteen different isolates exhibiting maximum formation of halos (zone of solubilization) around the bacterial colonies were selected for quantitative estimations of P-solubilization. Quantitative estimations for P-solubilization were analyzed for up to 10 days at intervals of 24 h. Maximum solubilization from 89.3 +/- A 3.1 to 164.1 +/- A 4.1 mu g ml(-1) was observed after 6 days of incubation in six of all isolates, while the isolate NII-1020 showed maximum P-solubilization. The increase in solubilization coincided with the drop in pH. Many of these species showed wide range of tolerance to temperature, pH, and salt concentrations. Further, 16S rRNA gene sequence analyses were carried to identify the bacterial groups which are actively solubilized phosphate in vitro. Gene sequencing results reveal that all isolates were clustered into six different actinobacterial genera: Streptomyces, Microbacterium, Angustibacter, Kocuria, Isoptericola, and Agromyces. The presence of phosphate-solubilizing microorganisms and their ability to solubilize phosphate were indicative of the important role played by bacteria in the biogeochemical cycle of phosphorus and the plant growth in coastal ecosystems.

Anti-fungal potentials of extracellular metabolites of western ghats isolated streptomyces sp NII 1006 against moulds and yeasts - Jayamurthy, Himani; Sajna, Kuttavan Valappil; Dastager, Syed Gulam; Pandey, Ashok (Indian Journal of Experimental Biology, 2014)
Realization of hazardious effects of chemical fungicides has led to an interest in the usage of biocontrol agents. The present study, therefore, evaluates the biocontrol efficacy of Western Ghats (India) soil bacterial isolates. A potential strain NII 1006 was evaluated for its antagonistic property against a diverse range of moulds and yeasts. The strain was characterized morphologically, biochemically and molecularly, which revealed the isolate belonged to Streptomyces genus. Organic solvent extracts of NII 1006 culture filtrates inhibited the growth of the test pathogens indicating that growth suppression was due to extracellular anti-fungal metabolites present in the culture filtrates. The strain produced extracellular chitinase enzyme in addition to some stable partially purified anti-fungal compounds. Morphological changes such as hyphae degradation into debris and abnormal shapes were observed in test fungi and yeast grown on potato dextrose broth that contained the NII 1006 culture filtrate. The cell free supernatant has a tolerance to wide range of pH, temperature and enzymes such as lipase and protease. The biocontrol potential of NII 1006 strain may be correlated significantly with their ability to produce antibiotics as well as extracellular hydrolytic enzymes particularly chitinolytic enzyme.
Keywords: Anti-fungal activity; Biocontrol; Extracellular anti-fungal metabolites; Streptomyces

Arthrobacter enclensis sp. nov., isolated from sediment sample - Dastager, Syed Gulam; Qin, Liu; Tang, Shan-Kun; Krishnamurthi, Srinivasan; Lee, Jae-Chan; Li, Wen-Jun (Archives of Microbiology, 2014)
A novel bacterial strain designated as NIO-1008(T) was isolated from marine sediments sample in Chorao Island India. Cells of the strains were gram positive and non-motile, displayed a rod-coccus life cycle and formed cream to light grey colonies on nutrient agar. Strain NIO-1008(T) had the chemotaxonomic markers that were consistent for classification in the genus Arthrobacter, i.e. MK-9(H-2) (50.3 %), as the major menaquinone, and the minor amount of MK-7 (H-2-27.5 %), MK-8 (H-4-11.6 %) and MK-8 (H-2-10.4 %). anteiso-C-15:0, iso-C-15:0, iso-C-16:0 and C-15:0 were the predominant fatty acids. Galactose, glucose and rhamnose are the cell-wall sugars, and DNA G+C content was 61.3 mol%. Phylogenetic analysis, based on 16S rRNA gene sequencing, showed that the strains were most similar to Arthrobacter equi IMMIB L-1606(T), Arthrobacter chlorophenolicus DSM 12829(T), Arthrobacter defluvii KCTC 19209(T) and Arthrobacter niigatensis CCTCC AB 206012(T) with 98.5, 98.4, 98.0 and 97.8 %, respectively, and formed a separate lineage. Combined phenotypic data and DNA-DNA hybridization data supported the conclusion that strains NIO-1008(T) represent a novel species within the genus Arthrobacter, for which the name Arthrobacter enclensis sp. nov., is proposed. The type strain is NIO-1008(T) = (NCIM 5488(T) = DSM 25279(T)).
Keywords: Arthrobacter; Chorao Island; Marine sediment; Polyphasic

Arthrobacter enclensis sp. nov., isolated from sediment sample (vol 196, pg 775, 2014) - Dastager, Syed Gulam; Liu, Qing; Tang, Shan-Kun; Krishnamurthi, Srinivasan; Lee, Jae-Chan; Li, Wen-Jun (Archives of Microbiology, 2014)

Bacillus enclensis sp nov., isolated from sediment sample - Dastager, Syed Gulam; Mawlankar, Rahul R.; Tang, Shan-Kun; Srinivasan, Krishnamurthi; Ramana, V. Venkata; Shouche, Yogesh S. (Antonie Van Leeuwenhoek International Journal of General and Molecular Microbiology, 2014)
A novel bacterial strain, designated SGD-1123(T) was isolated from Chorao Island, in Goa Province, India. The strain was found to be able to grow at 15-42 A degrees C, pH 5-12 and 0-12 % (w/v) NaCl. The whole cell hydrolysates were found to contain meso-diaminopimelic acid, galactose and arabinose. The major fatty acids were identified as iso-C-15:0 and anteiso-C-15:0, MK-7 was identified as the predominant menaquinone and the predominant polar lipids were identified as diphosphatidylglycerol, phosphatidylglycerol, phosphatidylethanolamine and an unidentified aminolipid. The genomic DNA G+C content was determined to be 44.6 mol%. Phylogenetic analysis based on 16S rRNA gene sequences placed the isolate within the genus Bacillus and further revealed that strain SGD-1123(T) had highest sequence similarity with Bacillus aquimaris, and forms a separate clade with its closest relatives i.e. B. aquimaris, Bacillus vietnamensis and Bacillus marisflavi, with which it shares 94.5, 94.1 and 94.1 % similarity respectively. The phylogenetic, chemotaxonomic and phenotypic analyses indicated that strain SGD-1123(T) represents a novel species within the genus Bacillus, for which the name Bacillus enclensis is proposed. The type strain is SGD-1123(T) (NCIM 5450(T)=CCTCC AB 2011125(T)).
Keywords: Bacillus sp; Marine sediment; Polyphasic

Culturable bacterial phylogeny from a shallow water hydrothermal vent of espalamaca (Faial, Azores) reveals a variety of novel taxa - Rajasabapathy, Raju; Mohandass, Chellandi; Colaco, Ana; Dastager, Syed Gulam; Santos, Ricardo Serrao; Meena, Ram Murti (Current Science, 2014)
Phylogenetic diversity of the 16S rRNA gene associated with the domain bacteria was examined at the level of operational taxonomic units (OTUs) using the rarefaction analysis from a newly identified shallow water hydrothermal vent, Espalamaca in the Azorean Island Faial (Horta), North Atlantic Ocean. Diluted sea water nutrient agar amended with metals manganese, lead, iron and element sulphur, could help in retrieving highest OTUs (95) from the vent and 39 OTUs from nonvent. Molecular tools implemented on bacterial census indicated the occupancy of gamma-Proteobacteria by 55.78%, alpha-Proteobacteria by 21.05% and 12.63% of Bacteroidetes in the total population. Occurrence of novel species maximized with alpha-Proteobacteria (11/20) followed by Bacteroidetes (5/12) signified the necessity of studying these groups to strengthen the biodiversity database. Shannon index (H') and the Chao I richness estimator illustrated a strong bacterial community in the venting area. The current study confers many bacterial genera which were not reported earlier in any of the shallow water vents and adds 33 new taxa to the database.
Keywords: Bacterial phylogeny; metals; novel taxa; rarefaction analysis; shallow vent

Development of bioconjugate from streptomyces tyrosinase and gold nanoparticles for rapid detection of phenol constituents - Zainab, Mazhari Bi Bi; Madhusudhan, D. N.; Raghavendra, H.; Dastager, Syed Gulam; Dayanand, Agsar (Indian Journal of Experimental Biology, 2014)
Most of the phenol compounds are toxic and have been considered as hazardous pollutants. Several physicochemical and biological methods are available to detect and monitor the phenol pollutants in water and soil. In the present study, phenol constituents of winery, paper and plastic industrial effluents were successfully detected employing tyrosinase-gold nanoparticles bioconjugate. The synthesis of extracellular tyrosinase and gold nanoparticles was achieved by a single isolate of Streptomyces sp. DBZ-39. Enhanced production (369.41 IU) of tyrosinase was produced in submerged bioprocess employing response surface method with central composite design. Extracellular gold nanoparticles synthesized (12-18 nm) by Streptomyces sp. DBZ-39 were characterized with TEM, EDAX and FTIR analysis. A rapid detection (within 10 min) of phenol constituents from winery effluents was achieved by bioconjugate, when compared to tyrosinases and gold nanoparticles independently. Streptomyces tyrosinase could exhibit relatively a better performance than commercially available mushroom tyrosinase in the detection of phenol constituents. Winery effluent has shown much higher content (0.98 O.D) of phenol constituents than paper and plastic effluents based on the intensity of color and U.V absorption spectra.
Keywords: Bioconjugate; gold nanoparticles; Phenol detection; Streptomyces; Tyrosinase

Domibacillus enclensis sp nov., isolated from marine sediment, and emended description of the genus domibacillus - Sonalkar, Vidya V.; Mawlankar, Rahul R.; Krishnamurthi, Srinivasan; Tang, Shan-Kun; Dastager, Syed Gulam (International Journal of Systematic and Evolutionary Microbiology, 2014)
A novel red-pigmented bacterial strain, designated NIO-1016(T), was isolated from a sediment sample from Chorao Island, India and was investigated by a polyphasic taxonomic approach. The strain was Gram-reaction-positive, strictly aerobic, motile and catalase-positive and produced spherical to slightly ellipsoidal endospores with subterminal position on swollen sporangia. The genomic DNA G+C content was 46.9 molok. The major fatty acids were anteiso-C-15:0, anteiso-C-17:0, iSO-C-15:0 and C-16:0. The predominant quinones were MK-6 (89.3 %) and MK-7 (8.7 %). The polar lipids consisted of diphosphatidylglycerol, phosphatidylglycerol, and an unidentified phospholipid. meso-Diaminopimelic acid (type My) was present in the cell-wall peptidoglycan and the major whole-cell sugars were glucose and ribose. The closest phylogenetic neighbours were identified as Domibacillus robiginosus DSM 25058(T) (98.0% similarity) and Domibacillus indicus DSM 28032(T) (97.2% similarity), other species of the genus Bacillus displayed below 96% similarity. Phylogenetic, physiological, biochemical and morphological differences between strain NI0-1016(T) and its closest neighbours indicate that this strain represents a novel species in the genus Domibacillus in the family Bacillaceae for which the name Domibacillus enclensis sp. nov. is proposed with the type species N10-1016(T) (=DSM 25145(T)=NCIM 5462(T)=CCTCC AB 2011121(T)).

Fictibacillus enclensis sp nov., isolated from marine sediment - Dastager, Syed Gulam; Mawlankar, Rahul R.; Srinivasan, Krishnamurthi; Tang, Shan-Kun; Lee, Jae-Chan; Ramana, V. Venkata; Shouche, Yogesh S. (Antonie Van Leeuwenhoek International Journal of General and Molecular Microbiology, 2014)
A novel Gram-positive strain, designated NIO-1003(T), was isolated from a marine sediment sample collected from the Chorao Island, Goa Provence, India. Strain NIO-1003(T) was found to be strictly aerobic, motile, endospore-forming rods. Phylogenetic analysis based on 16S rRNA gene sequences indicated that strain NIO-1003(T) belongs to the genus Fictibacillus and to be most closely related to Fictibacillus rigui KCTC 13278(T), Fictibacillus solisalsi KCTC 13181(T) and Fictibacillus barbaricus DSM 14730(T) with 98.2, 98.0 and 97.2 % similarity and 25, 28, 39 nucleotide differences respectively. Strain NIO-1003(T) was characterized by having cell-wall peptidoglycan based on meso-diaminopimelic acid and MK-7 as the predominant menaquinone. The polar lipid profile exhibited the major compounds diphosphatidylglycerol, phosphatidylglycerol and phosphatidylethanolamine. In addition, minor amounts of an aminophospholipid were detected. The major fatty acids were identified as ai-C-15:0, iso-C-15:0, ai-C-17:0 and C-16:0, supporting the grouping of strain NIO-1003(T) into the family Bacillaceae. The DNA G+C content of strain NIO-1003(T) was determined to be 42.6 mol%. On the basis of phenotypic properties, phylogeny and DNA-DNA hybridisation analysis, strain NIO-1003(T) is considered to represent a novel species of the genus Fictibacillus for which the name Fictibacillus enclensis sp. nov. is proposed. The type strain is NIO-1003(T) (= NCIM 5458(T) = DSM 25142(T)).
Keywords: Chorao Island; Fictibacillus sp.; Polyphasic taxonomy

Kocuria indica sp nov., isolated from a sediment sample - Dastager, Syed Gulam; Tang, Shan-Kun; Srinivasan, Krishnamurthi; Lee, Jae-Chan; Li, Wen-Jun (International Journal of Systematic and Evolutionary Microbiology, 2014)
An actinobacterial strain was isolated from a sediment sample from Chorao Island, in Goa province, India, and subjected to a taxonomic investigation. The isolate, designated NIO-1021(T), was a Gram-stain positive, aerobic, non-motile and coccoid. Strain NIO-1021(T) was identified as a member of the genus Kocuria by a polyphasic approach. Strain NIO-1021(T) could be differentiated from other members of the genus Kocuria on the basis of physiology and 16S rRNA gene sequence analysis. The 16S rRNA gene sequence similarity of strain NIO-1021(T) to the most closely related species, Kocuria marina KCTC 9943(T), was 98.6% with 19 nt differences). Furthermore, DNA-DNA hybridization analysis revealed that the novel strain had lower relatedness with the type strains of other members of the genus Kocuria. The strain formed a monophyletic clade with K. marina with 100% bootstrap values. The major phospholipids were phosphatidylglycerol, diphosphatidylglycerol and two unidentified lipids. The predominant menaquinone was MK-7(H-2). The major fatty acids were anteiso-C-15:0, iso-C-(16:0) and anteiso-C-17:0. The DNA G+C content of strain NIO-1021(T) was 60.5 mol%. Chemotaxonomic and phylogenetic properties of the strain were consistent with its classification as representing a member of the genus Kocuria. On the basis of phenotypic, chemotypic and molecular characteristics, strain NIO-1021(T) is considered to represent a novel species of the genus Kocuria, for which the name Kocuria indica sp. nov. is proposed, with strain NIO-1021(T) (=NCIM 5455(T)=DSM 25126(T)=CCTCC AA 209050(T)) as the type strain.

Rhodococcus enclensis sp nov., a novel member of the genus rhodococcus - Dastager, Syed Gulam; Mawlankar, Rahul R.; Tang, Shan-Kun; Krishnamurthi, Srinivasan; Ramana, V. Venkata; Joseph, Neeta; Shouche, Yogesh S. (International Journal of Systematic and Evolutionary Microbiology, 2014)
A novel actinobacterial strain, designated, NIO-1009(T), was isolated from a marine sediment sample collected from Chorao Island, Goa, India. Phylogenetic analysis comparisons based on 16S rRNA gene sequences between strain MO-1009(T) and other members of the genus Rhodococcus revealed that strain NI0-1009(T) had the closest sequence similarity to Rhodococcus kroppenstedtii DSM 44908(T) and Rhodococcus corynebacterioides DSM 20151(T) with 99.2 and 99.1%, respectively. Furthermore, DNA-DNA hybridization results showed that R. kroppenstedtii DSM 44908(T) and R. corynebacterioides DSM 20151(T) were 39.5 (3.0%) and 41.7 (2.0%) with strain NIO-1009(T), respectively, which were well below the 70% limit for any novel species proposal. Phylogenetically strain NIO-1009(T) forms a stable clade with and R. kroppenstedtii DSM 44908(T) and R. corynebacterioides DSM 201511 with 100% bootstrap values. Strain NI-1009(T) contained meso-diaminopimelic acid as the diagnostic diamino acid and galactose and arabinose as the cell wall sugars. The major fatty acids were C-16:0, C-18:1 omega 9c, C-16:1(omega 6C and/or omega 7c) and 10-methyl C-18:0. The only menaquinone detected was MK-8(H-2), while the major polar lipids were diphosphatidylglycerol, phosphatidylethanolamine, phosphatidylglycerol, phosphatidylinositol, phosphatidylinositol mannoside and one unknown phospholipid. The G + C content of the genomic DNA was 66.9 molok. The phenotypic and genotypic data showed that strain NIO-1009(T) warrants recognition as a novel species of the genus Rhodococcus for which the name Rhodococcus enclensis sp. nov., is proposed; the type strain is NIO-1009(T) (=NCIM 5452(T)=DSM 45688(T)).

Roseovarius azorensis sp nov., isolated from seawater at espalamaca, azores - Rajasabapathy, Raju; Mohandass, Chellandi; Dastager, Syed Gulam; Liu, Qing; Thi-Nhan Khieu; Chu Ky Son; Li, Wen-Jun; Colaco, Ana (Antonie van Leeuwenhoek International Journal of General and Molecular Microbiology, 2014)
A Gram-negative, motile, non-spore forming, rod shaped aerobic bacterium, designated strain SSW084(T), was isolated from a surface seawater sample collected at Espalamaca (38A degrees 33'N; 28A degrees 39'W), Azores. Growth was found to occur from 15 to 40 A degrees C (optimum 30 A degrees C), at pH 7.0-9.0 (optimum pH 7.0) and with 25-100 % seawater or 0.5-7.0 % NaCl in the presence of Mg2+ and Ca2+; no growth was found with NaCl alone. Colonies on seawater nutrient agar were observed to be punctiform, white, convex, circular, smooth, and translucent. Strain SSW084(T) did not grow on Zobell marine agar and tryptic soy agar even when seawater supplemented. The major respiratory quinone was found to be Q-10 and the G + C content was determined to be 61.9 mol%. Phylogenetic analysis based on the 16S rRNA gene sequence indicated that strain SSW084(T) belongs to the genus Roseovarius and that its closest neighbours are Roseovarius tolerans EL-172(T), Roseovarius mucosus DFL-24(T) and Roseovarius lutimaris 112(T) with 95.7, 95.4 and 95.3 % sequence similarity respectively. The remaining species of Roseovarius showed < 95 % similarity. The polar lipids of strain SSW084(T) were determined to be phosphatidylethanolamine, diphosphatidylglycerol, phosphatidylglycerol, phosphatidylcholine, an unidentified lipid and one unidentified aminolipid. The major fatty acids identified were identified as C-18:1 omega 7c (52.5 %) and C-16:0 (13.8 %). On the basis of phenotypic, molecular and chemotaxonomic characteristics, strain SSW084(T) is considered to represent a novel species of the genus Roseovarius, for which Roseovarius azorensis sp. nov is proposed. The type strain is SSW084(T) (=KCTC 32421(T) = MTCC 11812(T)).
Keywords: Espalamaca; Polyphasic taxonomy; Roseovarius azorensis sp nov; Seawater

Bacillus encimensis sp nov isolated from marine sediment - Dastager, Syed Gulam; Mawlankar, Rahul R.; Mual, Poonam; Verma, Ashish; Krishnamurthi, Srinivasan; Joseph, Neeta; Shouche, Yogesh S. (International Journal of Systematic and Evolutionary Microbiology, 2015)
A Gram-stain-positive, rod-shaped, endospore-forming, aerobic bacterium designated SGD-V-25(T) was isolated from Veraval sediment sample, India. Strain SGD-V-25(T) was capable of growing at 25-50 degrees C (optimum 37 degrees C), pH 6-12 (optimum pH 7.0) and with 0-5 % (w/v) NaCl. The taxonomic position of this strain was deduced using a polyphasic approach and the 16S rRNA gene sequence analysis showed that the isolate belongs to the phylum Firmicutes, forming the cluster with Bacillus badius MTCC 1548(T), with which it shares highest similarity of 99.1 % with 13 nt differences. Other type strains of the genus Bacillus showed less than 96% similarity. The cell wall contained meso-diaminopimelic acid as the diagnostic diamino acid. The polar lipid profile of strain SGD-V-25(T) showed the presence of diphosphatidylglycerol, phosphatidylglycerol, phsophoglycolipid and two aminophospholipids. The predominant isoprenoid quinone was MK-7. The major cellular fatty acids were iso-C-15:0, anteiso-C-15:0, anteiso-C-17:0 iso-C-16:0, C-16:1 omega 11c and C-16:0. The genomic DNA G + C content of strain SGD-V-25(T) was 37.6 molok. On the basis of phenotypic characteristics, phylogenetic analysis and DNA-DNA hybridization, strain SGD-V-25(T) could be clearly distinguished from closely related members of the genus Bacillus, and the name Bacillus encimensis sp. nov., is proposed to accommodate this strain. The type strain is SGD-V-25(T) (= NCIM 5513(T)=DSM 28241(T)).

Bacillus filamentosus sp nov., isolated from sediment sample - Sonalkar, Vidya V.; Mawlankar, Rahul R.; Ramana, V. Venkata; Joseph, Neeta; Shouche, Yogesh S.; Dastager, Syed Gulam (Antonie Van Leeuwenhoek International Journal of General and Molecular Microbiology, 2015)
A novel Gram-stain positive, endospore-forming bacterium, designated SGD-14(T), was isolated from a marine sediment sample in Goa Province, India. Cells of the isolate were found to be strictly aerobic. Phylogenetic analysis based on 16S rRNA gene sequences indicated that strain SGD-14(T) showed a similarity of 99.5 % with Bacillus endophyticus and similarities to other Bacillus type strains were below 96 %. The whole-cell sugar pattern was found to consist of ribose, xylose and glucose. The predominant menaquinone was identified as MK-7 and the major fatty acids as anteiso-C-15:0, iso-C-15:0, iso-C-16:0, anteiso-C-17:0, C-16:0 and iso-C-14:0. The strain was found to grow optimally at 30 A degrees C and pH 7.0-7.5. DNA G + C content was determined to be 39.6 mol%. The phospholipid pattern was found to consist of diphosphatidylglycerol, phosphatidylglycerol and phosphatidylethanolamine. DNA-DNA hybridization studies between strain SGD-14(T) and B. endophyticus CIP106778(T) showed that strain SGD-14(T) exhibited < 70 % similarity with B. endophyticus CIP106778(T). Differences in phenotypic and chemotaxonomic characteristics between the novel strain and B. endophyticus CIP106778(T) further confirmed that this isolate represents novel species. Phylogenetic analysis showed that strain SGD-14(T) fits in the same clade with B. endophyticus with 100 % bootstrap values. Strain SGD-14(T) is therefore considered to represent a novel species of the genus Bacillus, for which the name Bacillus filamentosus sp. nov. is proposed. The type strain of Bacillus filamentosus is SGD-14(T) = (=NCIM 5491(T) = DSM 27955(T)).
Keywords: Bacillus; Filaments; Polyphasic; Sediment

Citreicella manganoxidans sp nov., a novel manganese oxidizing bacterium isolated from a shallow water hydrothermal vent in Espalamaca (Azores) - Rajasabapathy, Raju; Mohandass, Chellandi; Dastager, Syed Gulam; Liu, Qing; Li, Wen-Jun; Colaco, Ana (Antonie Van Leeuwenhoek International Journal of General and Molecular Microbiology, 2015)
A Gram-stain negative, non-motile, non-spore forming, aerobic and rod or narrow lemon-shaped bacterial strain, VSW210(T), was isolated from surface seawater in a shallow water hydrothermal vent region in Espalamaca (Azores). Strain VSW210(T) was found to grow optimally at 30 A degrees C, at pH 7 and in the presence of 2-6 % (w/v) NaCl. A neighbour-joining phylogenetic tree based on 16S rRNA gene sequences revealed that strain VSW210(T) clusters with the type strain Citreicella marina CK-I3-6(T) (sequence similarity value of 99.6 %), but DNA-DNA hybridization showed DNA-DNA relatedness between the strain VSW210(T) and C. marina CK-I3-6(T) to be 55.8 +/- A 3.2 %. The DNA G+C content of strain VSW210(T) was determined to be 67.4 mol%. The cellular fatty acid profiles of strain VSW210(T) was found to contain C-18:1 omega 7c (80.1 %) and C-16:0 (9.2 %). The major polar lipids in strain VSW210(T) were identified as phosphatidylcholine, phosphatidylethanolamine, phosphatidylglycerol, diphosphatidylglycerol and an unidentified phospholipid. Strain VSW210(T) was found to be able to oxidize soluble Mn(II) to insoluble MnO2, which was confirmed with LBB staining. Differential phenotypic properties and genetic uniqueness revealed that this strain VSW210(T) is distinguishable from other species of the genus Citreicella. On the basis of the data presented, strain VSW210(T) is considered to represent a novel species of the genus Citreicella, for which the name Citreicella manganoxidans sp. nov. is proposed. The type strain is VSW210(T) (=KCTC 32497(T) = MCC 2286(T)).
Keywords: Azores; Citreicella manganoxidans sp nov; Hydrothermal vent; Polyphasic taxonomy; Seawater

Deinococcus enclensis sp nov., isolated from a marine sediment sample - Thorat, Meghana N.; Mawlankar, Rahul R.; Sonalkar, Vidya V.; Ramana, V. Venkata; Joseph, Neeta; Shouche, Yogesh S.; Dastager, Syed Gulam (Antonie Van Leeuwenhoek International Journal of General and Molecular Microbiology, 2015)
A novel pale-pink coloured strain, designated NIO-1023(T), was isolated from a marine sediment sample from Chorao Island, Goa, India. The taxonomic position of strain NIO-1023(T) was investigated by using a polyphasic approach. The cells were observed to be Gram-stain positive, coccal shaped and non-spore forming. Phylogenetic analyses using the 16S rRNA gene sequence of the isolate indicated that the organism belongs to the genus Deinococcus. The strain NIO-1023(T) showed highest 16S rRNA gene sequence similarities with Deinococcus ficus (97.8 %), whereas other Deinococcus species showed less than 95 % sequence similarity. The DNA-DNA relatedness with respect to D. ficus CC-FR2-10(T) was 23.9 %. Chemotaxonomic data revealed that strain NIO-1023(T) contains only menaquinone MK-8 as the respiratory quinone and a complex polar lipid profile consisting of different unidentified glycolipids and polar lipids, two unknown phospholipids and three unknown phosphoglycolipids. As in other deinococci, one of these phosphoglycolipids was predominant in the profile. The predominant fatty acids were identified as C-17:1 w8c, C-16:1 w6c/w7c, C-15:1 w6c and C-17:1 w9c. The genomic DNA G + C content of strain NIO-1023(T) was determined to be 67.2 mol%. The biochemical and chemotaxonomic properties demonstrate that strain NIO-1023(T) represents a novel species, for which the name Deinococcus enclensis sp. nov. is proposed. The type strain is NIO-1023(T) (=DSM 25127(T) = NCIM 5456(T)).
Keywords: 16S rRNA; Deinococcus; Marine sediments; Polyphasic

Exiguobacterium enclense sp nov., isolated from sediment - Dastager, Syed Gulam; Mawlankar, Rahul R.; Sonalkar, Vidya V.; Thorat, Meghana N.; Mual, Poonam; Verma, Ashish; Krishnamurthi, Srinivasan; Tang, Shan-Kun; Li, Wen-Jun (International Journal of Systematic and Evolutionary Microbiology, 2015)
A Gram-stain-positive bacterium, designated strain NIO-1109(T), was isolated from a marine sediment sample from Chorao Island, Goa, India. Phenotypic and chemotaxonomic characteristics and data from phylogenetic analysis based on 16S rRNA gene sequences indicated that strain NIO-1109(T) was related to the genus Exiguobacterium. Strain NIO-1109(T) exhibited >98.0% 16S rRNA gene sequence similarity with respect to Exiguobacterium indicum HHS 31(T) (99.5%) and Exiguobacterium acetylicum NCIMB 9889(T) (99.1 %); the type strains of other species showed <98% similarity. Levels of DNA DNA relatedness between strain NIO-1109(T) and E. acetylicum DSM 20416(T) and E indicum LMG 23471(T) were less than 70% (33.0 +/- 2.0 and 37 +/- 32%, respectively). Strain NIO-1109(T) also differed from these two closely related species in a number of phenotypic traits. Based on phenotypic, chemotaxonomic and phylogenetic data, strain NIO-1109(T) is considered to represent a novel species of the genus Exiguobacterium, for which the name Exiguobacterium enclense sp. nov. is proposed. The type strain is NIO-1109(T) (=NCIM 5457(T)= DSM 25128(T)=CCTCC AB 2011124(T)).

Microbacterium enclense sp nov., isolated from sediment sample - Mawlankar, Rahul R.; Mual, Poonam; Sonalkar, Vidya V.; Thorat, Meghana N.; Verma, Ashish; Srinivasan, Krishnamurthi; Dastager, Syed Gulam (International Journal of Systematic and Evolutionary Microbiology, 2015)
A novel bacterium (strain NIO-1002(T)) belonging to the genus Microbacterium was isolated from a marine sediment sample in Chorao Island, Goa Province, India. Its morphology, physiology, biochemical features and 16S rRNA gene sequence were characterized. Cells of this strain were Gram-stain-positive, non-motile, non-spore-forming rods that formed yellow-pigmented colonies. It grew in 0-12 % (w/v) NaCl and at 25-37 degrees C, with optimal growth at 30 degrees C. Phylogenetic analysis based on 16S rRNA gene sequences indicated that strain NIO-1002(T) is associated with members of the genus Microbacterium, with highest sequence similarity with Microbacterium hominis CIP 105731(T) (98.1%) and Microbacterium testaceum KCTC 9103(T) (98.0 %). Within the phylogenetic tree, this novel strain shared a branching point with M. hominis CIP 105731(T). The DNA G+C content was 66.5 mol% and DNA DNA hybridization relatedness between NI-1002(T), M. hominis CIP 105731(T) and M. testaceum KCTC 9103(T) was 39.0 +/- 2.0 % and 41.0 +/- 2.0 %, respectively. The major fatty acids were ai-C-15:0, i-C-16:0 and al-C-17:0 and the diamino acid in the cell-wall peptidoglycan of NIO-1002(T) was lysine. Data obtained from DNA-DNA hybridization and chemotaxonomic phenotypic analysis support the conclusion that strain NIO-1002(T) represents a novel species within the genus Microbacterium. The name Microbacterium enclense sp. nov. is proposed, with NIO-1002(T) (=NCIM 5454(T)=DSM 25125(T)=CCTCC AB 2011120(T)) as the type strain.

Myroides indicus sp nov., isolated from garden soil - Ram, Hari; Kumar, Alok; Thomas, Lebin; Dastager, Syed Gulam; Mawlankar, Rahul R.; Singh, Ved Pal (International Journal of Systematic and Evolutionary Microbiology, 2015)
A novel aerobic, non-motile, rod-shaped, catalase-and oxidase-positive bacterial strain, designated UKS3(T), was isolated from garden soil, and subjected to polyphasic taxonomic analysis. Strain UKS3(T) formed whitish, viscous colonies on nutrient agar and was Gram-staining negative. Phylogenetic analysis, based on 16S rRNA gene sequence, showed that maximum pairwise similarity occurs with representatives of the genus Myroides. The most closely related species include Myroides marinus JS-08(T) (92.7 % sequence similarity), Myroides phaeus MY15(T) (92.7 %), Myroides odoratus DSM 2801(T) (91.5 %) and Myroides odoratimimus CCUG 39352(T) (91.4 %). Strain UKS3(T) contained menaquinone-6 (MK-6) as the major respiratory quinone and iso-C-15 : 0 (40.2 %), anteiso-C-15 : 0 (9.4 %) and iso-C-17 : 0 3-OH (8.5 %) as major fatty acids. Phosphatidylethanolamine, phospholipids and three aminolipids were the major polar lipids. The DNA G + C content of strain UKS3(T) was 36.8 +/- 2.0 mol%. On the basis of phenotypic, chemotaxonomic and molecular analysis, strain UKS3(T) represents a novel species of the genus Myroides, for which the name Myroides indicus sp. nov., is proposed. The type strain is UKS3(T) (= DSM 28213(T) = NCIM 5555(T)).

Nioella nitratireducens gen. nov., sp nov., a novel member of the family Rhodobacteraceae isolated from Azorean Island - Rajasabapathy, Raju; Mohandass, Chellandi; Yoon, Jung-Hoon; Dastager, Syed Gulam; Liu, Qing; Khieu, Thi-Nhan; Son, Chu Ky; Li, Wen-Jun; Colaco, Ana (Antonie Van Leeuwenhoek International Journal of General and Molecular Microbiology, 2015)
A novel Gram-negative, non-spore forming, rod-shaped aerobic bacterium, designated SSW136(T), was isolated from a surface seawater sample collected at Espalamaca (in Faial Island), Azores. Growth was found to occur from 10 to 37 A degrees C, pH 6.0-8.0, and with 2-11 % of NaCl. 16S rRNA gene sequence indicated that the strain SSW136(T) belongs to the family Rhodobacteraceae. Strain SSW136(T) exhibited 96.3, 95.9, 95.7 and 95.5 sequence similarity to the type strains Oceanicola litoreus M-M22(T), Roseovarius aestuarii SMK-122(T), Marivita geojedonensis DPG-138(T), and Pseudoruegeria aquimaris SW-255(T) respectively. Neighbour-joining and maximum-parsimony phylogenetic trees based on 16S rRNA gene sequences revealed that strain SSW136(T) was affiliated to the family Rhodobacteraceae and formed a separate branch. The G+C content was 63.5 mol%. The major respiratory quinone was found to be Q-10. The polar lipids of strain SSW136(T) consisted of phosphatidylcholine, phosphatidylethanolamine, phosphatidylglycerol, two unidentified aminolipids and three unidentified phospholipids. The major fatty acids were C-18:1 omega 7c (46.5 %), Cyclo-C-19:0 omega 8c (16.0 %) and C-16:0 (12.8 %). On the basis of the morphological, genotypic, chemotaxonomic characteristics and low DNA-DNA relatedness, strain SSW136(T) is proposed to represent a novel genus and novel species, Nioella nitratireducens gen. nov., sp. nov., in the family Rhodobacteraceae. The type strain is SSW136(T) (=KCTC 32417(T) = NCIM 5499(T)).
Keywords: Espalamaca; Nioella nitratireducens; Novel genus and species; Polyphasic taxonomy; Seawater

Nonomuraea indica sp nov., novel actinomycetes isolated from lime-stone open pit mine, India - Quadri, Syed Raziuddin; Tian, Xin-Peng; Zhang, Jing; Li, Jie; Nie, Guo-Xing; Tang, Shu-Kun; Al Ruwaili, Jamal; Agsar, Dayanand; Li, Wen-Jun; Dastager, Syed Gulam (Journal of Antibiotics, 2015)
A Gram-positive, aerobic, nonmotile actinomycete strain designated DRQ-2(T) was isolated from the soil sample collected from limestone open pit mine from the Gulbarga region, Karnataka province, India. Strain DRQ-2(T) was identified as a member of the genus Nonomuraea by a polyphasic approach. Strain DRQ-2(T) could be differentiated from other members of the genus Nonomuraea on the basis of physiology and 16S rRNA gene sequence analysis. The 16S rRNA gene sequence similarity of strain DRQ-2(T) showed highest sequence similarity to Nonomuraea muscovyensis DSM 45913(T) (99.1%), N. salmonea DSM 43678(T) (98.2%) and N. maheshkhaliensis JCM 13929(T) with 98.0%, respectively. Chemotaxonomic properties showing predominant menaquinones of MK-9 (H-4), MK-9(H-2) and MK-9(H-6), major polar lipids comprised diphosphatidylglycerol, phosphatidylmono methyl ethanolamine (PME), phosphatidylethanolamine (PE), hydroxy-PME (OH-PME), hydroxy PE (OH-PEE), phosphatidylglycerol (PG), ninhydrin-positive phosphoglycolipid and unknown phospholipid, fatty acids with major amounts of i-C-16:0, ai-C-15:0 and ai-C-17:0 supported allocation of the strain to the genus Nonomuraea. Results of DNA-DNA hybridization and physiological tests allowed genotypic and phenotypic differentiation of strain DRQ-2(T) from closely related species. The genomic DNA G+C content of the organism was 72.5 mol%. On the basis of phenotypic, chemotypic and molecular characteristics, strain DRQ-2(T) represents a novel species of the genus Nonomuraea, for which the name N. indica sp. nov. is proposed, with type strain DRQ-2(T) (= NCIM 5480(T) = CCTCC AA 209050(T)).

Vitellibacter nionensis sp nov., isolated from a shallow water hydrothermal vent - Rajasabapathy, Raju; Mohandass, Chellandi; Yoon, Jung-Hoon; Dastager, Syed Gulam; Liu, Qing; Thi-Nhan Khieu; Chu Ky Son; Li, Wen-Jun; Colaco, Ana (International Journal of Systematic and Evolutionary Microbiology, 2015)
A novel, Gram-stain-negative, non-motile, rod-shaped yellow bacterium, designated VBW088(T) was isolated from a shallow water hydrothermal vent in Espalamaca in the Azores. Phylogenetic analysis based on 16S rRNA gene sequences showed that strain VBW088(T) clustered with three type strains of species of the genus Vitellibacter and exhibited a sequence similarity of 97.3% with Vitellibacter soesokkakensis RSSK-12(T). However, strain VBW088(T) and V. soesokkakensis RSSK-12(T) exhibited low DNA-DNA relatedness (12.7 +/- 3.5 %). Strain VBW088(T) was positive for catalase and oxidase. Growth occurred at 10-37 degrees C, with the optimum at 80 degrees C, and at pH 6.0-8.0 (optimum pH 6.0) and in up to 5% (w/v) NaCl with optimum growth at 1-2% (w/v) NaCl. The major fatty acids (>10%) were iso-C-15:0 (33.5%) and iso-C-17:0 3-OH (32.0%). The polar lipids detected in strain VBW088(T) consisted of phosphatidylethanolamine, one unidentified aminolipid and three unidentified phospholipids. The DNA G+C content of strain VBW088(T) was 36.7 mol%. On the basis of phylogenetic inference, DNA-DNA relatedness, chemotaxonomic analysis and physiological data, the isolate represents a novel species of the genus Vitellibacter, for which the name Vitellibacter nionensis sp. nov. is proposed, with the type strain as VBW088(T). (=KCTC 32420(T)=MCC 2354(T)).

Actinorectispora indica gen. nov., sp nov isolated from soil, a member of the family pseudonocardiaceae - Quadri, Syed Raziuddin; Tian, Xin-Peng; Zhang, Jing; Al Ruwaili, Jamal; Hozzein, Wael N.; Agsar, Dayanand; Li, Wen-Jun; Dastager, Syed Gulam (International Journal of Systematic and Evolutionary Microbiology, 2016)
The taxonomic positions of three Gram-stain-positive, aerobic strains, designated YIM 75722, 75726 and 75728(T), and isolated from a soil sample collected from Kurnool of Andhra Pradesh province, India, were assessed using a polyphasic approach. Growth was observed at pH 7.0-10.0 (optimum pH 7.0), 15-28 degrees C (optimum 28 degrees C) and 0-8% (w/v) NaCl (grew without NaCl). Strains showed cylindrical spores with straight-chain morphology on aerial mycelium, but did not reveal sporangium-like structures or fragmentation of the substrate mycelium. Whole-cell hydrolysates of all strains contained galactose and ribose as the diagnostic sugars and meso-diaminopimelic acid as the diamino acid. The predominant menaquinone was MK-9(H-4); MK-9 (H-6) and MK-10 (H-4) were present in smaller amounts. The phospholipid pattern consisted mainly of diphosphatidylglycerol, phosphatidylglycerol and phosphatidylcholine. The major fatty acids were i-C-15: 0, ai-C-15: 0, i-C-17 : 0 and ai-C-17 : 0. The genomic DNA G+C content was 68.0 mol%. Phylogenetic analysis, based on 16S rRNA gene sequences, revealed that strain YIM 75728(T) should be placed within the family Pseudonocardiaceae, in which the strain formed a distinct lineage. The combination of phylogenetic analysis, phenotypic characteristics and chemotaxonomic data support the conclusion that strain YIM 75728(T) represents a novel species of a novel genus of the family Pseudonocardiaceae for which the name Actinorectispora indica gen. nov., sp. nov., is proposed. Strain YIM 75728(T) (=DSM 45410(T)=CCTCC AA 209065(T)) is the type strain of Actinorectispora indica. Strain YIM 75728(T) was considered as the type strain over the other two strains based on the highest sequence read length of the strain.

Antioxidative metabolites synthesized by marine pigmented vibrio sp and its protection on oxidative deterioration of membrane lipids - Pawar, Ravindra; Mohandass, Chellandi; Dastager, Syed Gulam; Kolekar, Yogesh M.; Malwankar, Rahul (Applied Biochemistry and Biotechnology, 2016)
Bacterial strain Vibrio sp. (PIGB 184) isolated from water samples of the Arabian Sea and identified through 16S rRNA demonstrated the production of pigmentary antioxidants with higher ABTS activities 90.9 +/- 0.42 % in comparison with the standard commercial pigmented antioxidant, quercetin 88.8 +/- 1.4 %. Antioxidative metabolites of this strain substantially inhibit the lipid peroxidation (LPO) reactions tested in sheep liver and brain. The antioxidant compounds produced by the Vibrio sp. (PIGB 184), analysed by GC-MS, reveals that it is composed mostly of phenol, 2,4-bis(1,1-dimethylethyl) and pyrrolo[1,2-a]pyrazine-1,4-dione,hexahydro-3-(2-methylpropyl). The interrelationship assessed between LPO and the phenolic compounds showed significant correlation with anti-LPO properties (R (2) = 0.9698 to 0.9861). These compounds are responsible for obstruction of harmful radical associated biochemical reactions in biological systems. Pigmented metabolites also tested for attributive biological properties against pathogenic bacteria showed prominent inhibition towards Gram-positive organisms (31.25 to 62.5 mu g ml(-1)). From this study, it may be suggested that the marine bacterium PIGB 184 could be used as a potential bio-resource for antioxidants and needs to be worked out for mass production.
Keywords: Antioxidants; Lipid peroxidation; Marine pigmented bacteria; Pathogen inhibition; Phenolics

Bacillus cellulasensis sp nov., isolated from marine sediment - Mawlankar, Rahul R.; Thorat, Meghana N.; Krishnamurthi, Srinivasan; Dastager, Syed Gulam (Archives of Microbiology, 2016)
A novel bacterial strain NIO-1130(T) was isolated from sediment sample taken from Chorao Island, Goa Province, India, and subjected to a taxonomic investigation. The strain was Gram-positive, aerobic, and motile. Phylogenetic analysis based on 16S rRNA gene sequences placed the isolate within the genus Bacillus and strain NIO-1130(T) showed highest sequence similarity with Bacillus halosaccharovorans DSM 25387(T) (98.4 %) and Bacillus niabensis CIP 109816(T) (98.1 %), whereas other Bacillus species showed < 97.0 % similarity. Tree based on gyrB gene sequence revealed that strain bacillus group. The major menaquinone was MK-7 and the predominant cellular fatty acids were iso-C-15:0, anteiso-C-15:0, iso-C-17:0, and anteiso-C-17:0. The strain showed a DNA G+C content of 39.9 mol%. DNA-DNA hybridization studies revealed that strain NIO-1130(T) exhibits 70 % similarity with Bacillus halosaccharovorans DSM 25387(T) and Bacillus niabensis CIP 109816T. On the basis of physiological, biochemical, chemotaxonomic and phylogenetic analyses, we consider the isolate to represent a novel species of the genus Bacillus, for which the name Bacillus cellulasensis sp. nov., is proposed. The type strain is NIO-1130(T) (=NCIM 5461(T) = CCTCC AB 2011126(T)).
Keywords: Bacillus sp; Cellulase; Marine sediment; Polyphasic taxonomy

Complete metagenome sequencing based bacterial diversity and functional insights from basaltic hot spring of Unkeshwar, Maharashtra, India - Mehetre, Gajanan T.; Paranjpe, Aditi S.; Dastager, Syed Gulam; Dharne, Mahesh S. (Genomics Data, 2016)
Unkeshwar hot springs are located at geographical South East Deccan Continental basalt of India. Here, we report the microbial community analysis of this hot spring using whole metagenome shotgun sequencing approach. The analysis revealed a total of 848,096 reads with 212.87Mbps with 50.87% G+C content. Metagenomic sequences were deposited in SRA database with accession number (SUB1242219). Community analysis revealed 99.98% sequences belonging to bacteria and 0.01% to archaea and 0.01% to Viruses. The data obtained revealed 41 phyla including bacteria and Archaea and including 719 different species. In taxonomic analysis, the dominant phyla were found as, Actinobacteria (56%), Verrucomicrobia (24%), Bacteriodes (13%), Deinococcus-Thermus (3%) and firmicutes (2%) and Viruses (2%). Furthermore, functional annotation using pathway information revealed dynamic potential of hot spring community in terms of metabolism, environmental information processing, cellular processes and other important aspects. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis of each contig sequence by assigning KEGG Orthology (KO) numbers revealed contig sequences that were assigned to metabolism, organismal system, Environmental Information Processing, cellular processes and human diseases with some unclassified sequences. The Unkeshwar hot springs offer rich phylogenetic diversity and metabolic potential for biotechnological applications.

Editorial: actinobacteria in special and extreme habitats: diversity, function roles, and environmental adaptations - Qin, Sheng; Li, Wen-Jun; Dastager, Syed Gulam; Hozzein, Wael N. (Frontiers in Microbiology, 2016)
Keywords: actinobacteria; activities; diversity; environmental adaptation; omics technologies; special and extreme environments

Investigation of microbial diversity in geothermal hot springs in Unkeshwar, India, based on 16S rRNA amplicon metagenome sequencing - Mehetre, Gajanan T.; Paranjpe, Aditi; Dastager, Syed Gulam; Dharne, Mahesh S. (Genome Announcements, 2016)
Microbial diversity in geothermal waters of the Unkeshwar hot springs in Maharashtra, India, was studied using 16S rRNA amplicon metagenomic sequencing. Taxonomic analysis revealed the presence of Bacteroidetes , Proteobacteria , Cyanobacteria , Actinobacteria , Archeae , and OD1 phyla. Metabolic function prediction analysis indicated a battery of biological information systems indicating rich and novel microbial diversity, with potential biotechnological applications in this niche.

Reclassification of bacillus isronensis shivaji et al. 2009 as solibacillus isronensis comb. nov and emended description of genus solibacillus krishnamurthi et al. 2009 - Mual, Poonam; Singh, Nitin Kumar; Verma, Ashish; Schumann, Peter; Krishnamurthi, Srinivasan; Dastager, Syed Gulam; Mayilraj, Shanmugam (International Journal of Systematic and Evolutionary Microbiology, 2016)
An investigation into the taxonomic position of Bacillus isronensis MTCC 7902(T) revealed that the strain shares a common phylogenetic lineage with Solibacillus silvestris MTCC 10789(T). It displays considerable overlap in phenotypic properties with the genus Solibacillus, including endospore shape and position, oxidase and catalase activities, presence of iso-C-15 : 0, C-16 : (1)omega 7c alcohol and iso-C-17 : 1 omega 7c as major cellular fatty acids, A4 alpha-type cell-wall peptidoglycan, polar lipids and menaquinone pattern. These features reinforce the findings of molecular phylogenetic analyses based on 16S rRNA gene, gyrB gene and 16S-23S internal transcribed spacer (ITS) region sequences and, in line with the recommendations of Kampfer et al. [Int J Syst Evol Microbiol 56 (2006), 781-786], provide justification for the transfer of Bacillus isronensis from the genus Bacillus to Solibacillus as Solibacillus isronensis comb. nov. The type strain is B3W22(T) (=MTCC 7902(T) =DSM 21046(T) =JCM 13838(T)). An emended description of the genus Solibacillus is also provided.

Streptomyces lonarensis sp nov., isolated from lonar lake, a meteorite salt water lake in India - Sharma, Trupti K.; Mawlankar, Rahul R.; Sonalkar, Vidya V.; Shinde, Vidhya K.; Zhan, Jing; Li, Wen-Jun; Rele, Meenakshi V.; Dastager, Syed Gulam; Kumar, Lalitha Sunil (Antonie Van Leeuwenhoek International Journal of General and Molecular Microbiology, 2016)
A novel alkaliphilic actinomycete, strain NCL716(T), was isolated from a soil sample collected from the vicinity of Lonar Lake, an alkaline salt water meteorite lake in Buldhana district of Maharashtra State in India. The strain was characterised using a polyphasic taxonomic approach which confirmed that it belongs to the genus Streptomyces. Growth was observed over a pH range of 7-11 at 28 A degrees C. The cell wall was found to contain ll-diaminopimelic acid and traces of meso-diaminopimelic acid. The major fatty acid components were identified as iso-C-16:0 (46.8 %), C-17:1 (12.4 %), anteiso-C-15:0 (5.1 %) and anteiso-C-17:1 (4.8 %). The major polar lipids were identified as diphosphatidylglycerol, phosphatidylethanolamine, phosphatidylglycerol and phosphatidylinositol. The major menaquinones were determined to be MK-9 (H-6) (70.3 %), MK-9 (H-4) (15.5 %) and MK-9 (H-8) (7.2 %). The G+C content of the DNA of the type strain was determined to be 71.4 mol %. The 16S rRNA gene sequence has been deposited in GenBank with accession number FJ919811. Although the 16S rRNA gene sequence analysis revealed that strain NCL716(T) shares > 99 % similarity with that of Streptomyces bohaiensis strain 11A07(T), DNA-DNA hybridization revealed only 33.2 +/- A 3.0 % relatedness between them. Moreover, these two strains can be readily distinguished by some distinct phenotypic characteristics. Hence, on the basis of phenotypic and genetic analyses, it is proposed that strain NCL716(T) represents a novel species of the genus Streptomyces, for which the name Streptomyces lonarensis sp. nov., is proposed. The type strain is NCL 716(T) (=DSM 42084(T) = MTCC 11708(T) = KCTC 39684(T)).
Keywords: Alkaliphile; DDH analysis; Polyphasic taxonomy; Streptomyces lonarensis sp nov.

Anti-microbial activity of chrysomycin a produced by streptomyces sp. against mycobacterium tuberculosis - Balaji, Muralikrishnan; Dan, Vipin Mohan; Joseph, Vinodh; Jamsheena, Vellekkatt; Ramachandran, Ranjit; Thomas, Sabu; Dastager, Syed Gulam; Kumar, K. Santhosh; Lankalapalli, Ravi Shankar; Kumar, R. Ajay (RSC Advances, 2017)
Limited efficacy of the BCG (Bacillus Calmette–Guérin) vaccine against adult tuberculosis and the emergence of resistance to existing anti-tuberculosis drugs compel discovery of novel antibiotics against Mycobacterium tuberculosis. Actinomycetes are still an attractive platform for the discovery of new antimicrobials, especially from untapped natural hotspots, despite the belief that they are an exhausted resource after repeated re-discoveries. Herein we report the isolation and identification of chrysomycin A from an actinomycete isolated from a coastal area in Kerala. We show for the first time that it has antimycobacterial activity. It was found to be bactericidal to planktonic and intracellular M. tuberculosis with an MIC of 3.125 μg mL⁻¹; it is non-hemolytic and has negligible cytotoxicity. The actinomycete that produces chrysomycin A was found to be a Streptomyces sp. through 16S rRNA gene sequencing.

Biosurfactant surfactin as a kinetic promoter for methane hydrate formation - Bhattacharjee, Gaurav; Barmecha, Vivek; Pradhan, Darshan; Naik, Rajesh; Zare, Kirti; Mawlankar, Rahul R.; Dastager, Syed Gulam; Kushwaha, Omkar Singh; Kumar, Rajnish (Energy Procedia, 2017)
In the present study, the effect of the biosurfactant Surfactin on methane hydrate formation kinetics was studied. Initially, several marine derived species were screened for the presence of Surfactin. The polymerase chain reaction technique was used as the preliminary screening step for Surfactin which was then followed up by a couple of different assays to provide conclusive evidence of the same. Based on these tests, the D-9 bacterial strain was identified as a producer of Surfactin. Once the presence of Surfactin had been proven, its effect on methane hydrate formation kinetics was investigated upon by carrying out hydrate formation experiments in a stirred tank reactor. The cell free supernatant containing Surfactin was itself used as the hydrate forming solution without any further processing. It was found that the presence of Surfactin in the system greatly enhances hydrate formation kinetics as compared to pure water. In fact the kinetics in presence of Surfactin also surpassed that obtained with 1 wt% SDS, the most commonly used synthetic kinetic hydrate promoter. This basic study can pave the way for more sophisticated research on the use of biosurfactants as kinetic promoters with a view on rapid methane hydrate formation kinetics for applications such as methane separation, storage and transport.

Examination into the taxonomic position of Bacillus thermotolerans Yang et al., 2013, proposal for its reclassification into a new genus and species Quasibacillus thermotolerans gen. nov., comb. nov. and reclassification of B. encimensis Dastager et al., - Verma, Ashish; Pal, Yash; Khatri, Indu; Ojha, Anup Kumar; Gruber-Vodicka, Harald; Schumann, Peter; Dastager, Syed Gulam; Subramanian, Srikrishna; Mayilraj, Shanmugam; Krishnamurthi, Srinivasan (Systematic and Applied Microbiology, 2017)
Two novel Gram-staining positive, rod-shaped, moderately halotolerant, endospore forming bacterial strains 5.5LF 38TD and 5.5LF 48TD were isolated and taxonomically characterized from a landfill in Chandigarh, India. The analysis of 16S rRNA gene sequences of the strains confirmed their closest identity to Bacillus thermotolerans SgZ-8T with 99.9% sequence similarity. A comparative phylogenetic analysis of strains 5.5LF 38TD, 5.5LF 48TD and B. thermotolerans SgZ-8(T) confirmed their separation into a novel genus with B. badius and genus Domibacillus as the closest phylogenetic relatives. The major fatty acids of the strains are iso-C15:0 and iso-C16:0 and MK-7 is the only quinone. The major polar lipids are diphosphatidylglycerol, phosphatidylglycerol and phosphatidylethanolamine. The digital DNA-DNA hybridization (DDH) and ortho average nucleotide identity (ANI) values calculated through whole genome sequences indicated that the three strains showed low relatedness with their phylogenetic neighbours. Based on evidences from phylogenomic analyses and polyphasic taxonomic characterization we propose reclassification of the species B. thermotolerans into a novel genus named Quasibacillus thermotolerans gen. nov., comb. nov with the type strain SgZ-8(T) (=CCTCC AB2012108(T)=KACC 16706(T)). Further our analyses also revealed that B. encimensis SGD-V-25(T) is a later heterotypic synonym of Bacillus badius DSM 23(T).

Investigation into the taxonomy of “ B. aminovorans” and its reclassification to the genus Domibacillus as Domibacillus aminovorans sp. nov. - Verma, Ashish; Ojha, Anup Kumar; Pal, Yash; Kumari, Parveen; Schumann, Peter; Gruber-Vodicka, Harald; Dastager, Syed Gulam; Natarajan, Ramesh Kumar; Mayilraj, Shanmugam; Krishnamurthi, Srinivasan (Systematic and Applied Microbiology, 2017)
The species "Bacillus aminovorans" was categorized as species Incertae Sedis meaning taxa with uncertain taxonomic position because of insufficient description of phenotypic properties and lack of understanding of its phylogenetic relationship (Claus and Berkeley [5]). In this study two strains "B. aminovorans" DSM 1314T and DSM 4337 were phenotypically and phylogenomically analyzed. The strains are Gram-staining-positive, spore forming rods and unable to utilize/ferment most of the sugars tested except glucose. The major fatty acids are anteiso-C15:0 and iso-C15:0. The major polar lipids are diphosphatidylglycerol, phosphatidylglycerol and an aminophosphoglycolipid. The cell wall peptidoglycan is of A1γ type with meso-Dpm as the diamino acid. The menaquinone type present is MK-6. The G+C content of the genomic DNA of the type strain is 40.8mol%. These characteristics were found to be in line with description of the genus Domibacillus. Moreover phylogenetic analysis based on 16S rRNA gene sequence retrieved "B. aminovorans" within the genus Domibacillus with D. antri XD 80T as the closest relative. Additionally genome sequencing of the strains and their comparison with whole genome sequences of other Domibacillus spp. confirmed their distinctiveness and separate species status within the genus based on parameters of genome to genome distance calculator (GGDC) and average nucleotide identity (ANI) values. Therefore a novel species Domibacillus aminovorans sp. nov. (DSM 1314T =LMG 16796T) is proposed.
Keywords: 16S rRNA; Domibacillus aminovorans; MALDI-TOF; ``Bacillus aminovorans''

Untapped bacterial diversity and metabolic potential within Unkeshwar hot springs, India - Mehetre, Gajanan T. (Archives of Microbiology, 2018)
Hot springs support diverse and interesting groups of microorganisms adapted to extreme conditions and gaining attention in biotechnological applications. However, due to limitations of cultivation methods, a majority of such extremophiles remain uncultivated and unexplored. The advent of multiple cultivation conditions and specialized culture media could possibly aid to access the unexplored microbial portion of hot springs. In the present study, different media and isolation strategies were applied to isolate hitherto unexplored bacterial taxa in the water samples collected from Unkeshwar hot springs, India. Molecular, phylogenetic and predictive functional characterization of the isolated bacterial population was done using 16S rRNA sequencing coupled with Tax4Fun tools. Furthermore, representative isolates were screened for important enzymes (cellulase, xylanase, amylase, and protease) and heavy metal tolerance (chromium, arsenic) properties. A total of 454 bacterial isolates obtained were mapped into 57 unique bacterial genera and 4 different bacterial phyla. Interestingly, 37 genera not previously isolated from Indian hot springs, were isolated for the first time in the present study. However, most of these genera (23 out of 37) were reported only in metagenomics studies from Indian and global hot springs. Furthermore, around 14 genera not previously cultivated and not detected in metagenomics studies of hot springs are documented here. The metabolic potential was ascertained by determining the abundance of specific genes using in silico based Tax4Fun tool, which identified around 315 metabolic pathways for metabolism of carbohydrates, synthesis of secondary metabolites and degradation of xenobiotic compounds. Bioprospection study revealed that 33 and 25 bacterial genera were positive for enzyme production and resistance to the heavy metals, respectively. The present study revealed the advantages of cultivation methods using a comprehensive multiple isolation approach for exploring untapped and unique bacterial diversity, and also utilities for various biotechnological and environmental applications.
Keywords: Bacterial diversity; Bioprospecting; Cultivation; Heavy metals; Untapped

Hydrophilic 3D interconnected network of bacterial nanocellulose/black titania photothermal foams as an efficient interfacial solar evaporator - Nabeela, Kallayi; Thorat, Meghana; Sumina, N. B.; Ramachandran, Animesh M.; Thomas, Reny Thankam; Preethikumar, Gopika; Mohamed, A. Peer; Asok, Adersh; Dastager, Syed Gulam; Pillai, Saju (ACS Applied Bio Materials, 2021)
The design and development of scalable, efficient photothermal evaporator systems that reduce microplastic pollution are highly desirable. Herein, a sustainable bacterial nanocellulose (BNC)-based self-floating bilayer photothermal foam (PTF<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; bottom: -0.25em; font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">b) is designed that eases the effective confinement of solar light for efficient freshwater production via interfacial heating. The sandwich nanoarchitectured porous bilayer solar evaporator consists of a top solar-harvesting blackbody layer composed of broad-spectrum active black titania (BT) nanoparticles embedded in the BNC matrix and a thick bottom layer of pristine BNC for agile thermal management, the efficient wicking of bulk water, and staying afloat. A decisive advantage of the BNC network is that it enables the fabrication of a lightweight photothermal foam with reduced thermal conductivity and high wet strength. Additionally, the hydrophilic three-dimensional (3D) interconnected porous network of BNC contributes to the fast evaporation of water under ambient solar conditions with reduced vaporization enthalpy by virtue of intermediated water generated via a BNC–water interaction. The fabricated PTF<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; bottom: -0.25em; font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">b is found to yield a water evaporation efficiency of 84.3% (under 1054 W m<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">–2) with 4 wt % BT loading. Furthermore, scalable PTF<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; bottom: -0.25em; font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">b realized a water production rate of 1.26 L m<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">–2 h<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">–1 under real-time conditions. The developed eco-friendly BNC-supported BT foams could be used in applications such as solar desalination, contaminated water purification, extraction of water from moisture, etc., and thus could address one of the major present-day global concerns of drinking water scarcity.

Editorial: microbial biodiversity and bioprospecting in polar ecosystems in the genomics era - Rizzo, Carmen; Dastager, Syed Gulam; Ay, Hilal (FRONTIERS IN MICROBIOLOGY, 2024)
Keywords: diversity; FJORD

Integrated genomic and functional analysis of Streptomyces sp. UP1A-1 for bacterial wilt control and solanaceae yield increase - Kaari, Manigundan; Manikkam, Radhakrishnan; Joseph, Jerrine; Krishnan, Sakthivel; Annamalai, Kishore Kumar; Khan, Abujunaid; Rajput, Vinay; Dastager, Syed Gulam; Dharne, Mahesh S.; Umar, Md; Venugopal, Gopikrishnan; Alexander, Balamurugan (Gene Reports, 2024)
<em style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">Ralstonia solanacearum<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> is one of the most destructive soil-borne pathogen, causing bacterial wilt to the solanaceae vegetables. <em style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">Streptomyces<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> sp. UP1A-1 isolated from healthy solanaceae rhizosphere soil, exhibited the lowest disease incidence and increased fruit yield of solanaceae vegetables. However, the genomic and functional properties of UP1A-1 are unclear. Therefore, we conducted the present study to elucidate the genomic characteristics of UP1A-1 by whole genome sequencing. The results indicate that the genome of <em style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">Streptomyces<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> sp. UP1A-1 consists of 8,252,902 bp and contains 72.42 % G + C. We identified the genes that confer plant growth promoting (PGP) function, which include those involved in siderophore production, indole-3-acetic acid biosynthesis, phosphate solubilization, nitrogen metabolism, and potassium metabolism. We also identified several other genes, such as chitinase, peroxidase, superoxide dismutase, catalase, proline biosynthesis, and glucose dehydrogenase, which are believed to be involved in the control of wilt disease. These genes revealed that the strain UP1A-1 has physiologically adapted to varied environmental conditions and could potentially control both abiotic and biotic stresses.

Genomic insights and biotechnological potential of “Mesobacillus aurantius” strain S13: a canthaxanthin pigment-producing bacterium - Karthik, Shankar; Raman, Gurusamy; Srinivasan, Arumugam; Dastager, Syed Gulam; Wagh, Vasudev; Ayyadurai, Niraikulam (Gene Reports, 2025)
<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">This study explores the discovery and characterization of pigments, from a microorganism thriving under environmentally challenging conditions. Utilizing a polyphasic taxonomic approach, we successfully isolated and identified a bacterial strain S13 within the <em style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">Mesobacillus<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> genus and Bacillaceae family, designated as “<em style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">Mesobacillus aurantius<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">” S13. We confirmed the species based on comprehensive phenotypic, physiological, and biochemical analyses, molecular phylogenetics, DNA–DNA hybridization, average nucleotide identity, and whole-genome sequencing. The strain S13 (MTCC13141 = VKM B-3583 = NBIMCC 9084) possesses a 4.81 Mbp genome that encodes genes for pigment production. Notably, this study uses various spectroscopic methods to characterize canthaxanthin, an orange pigment and delineates its biosynthetic pathway from the genome of S13. The methylerythritol phosphate (MEP) pathway and canthaxanthin biosynthesis genes highlight the capacity of the bacterium to synthesize crucial isoprenoids and terpenoids, including canthaxanthin. This research provides a detailed account of the isolation, characterization, and taxonomic classification of “<em style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">Mesobacillus aurantius<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">” S13 and underscores the potential biotechnological applications of the bacterium in producing pharmaceuticals, biofuels, and cosmetics. Therefore, “<em style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">Mesobacillus aurantius<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">” S13 is a potentially valuable microbial resource for the industrial production of isoprenoids and pigments.